Primitive Neuroectodermal Tumor in a Child with Human Immunodeficiency Virus Infection: A Rare Association. (30th June 2019) - Gupta, Aman; Bhattarai, Dharmagat; Thapa, Bishnu Kumar; Parkhi, Mayur; Vignesh, Pandiarajan; Vasishta, Rakesh K; Tripathi, Manjul; Vyas, Sameer; Gupta, Anju
Abstract: Children with human immunodeficiency virus (HIV) infection are reported to have various malignancies, most common being Non-Hodgkin lymphoma. Despite higher risk of malignancies, brain tumors are infrequently described in these children. We report Primitive Neuroectodermal tumor (PNET) in a young boy with HIV infection. PNET has never been described in association with HIV infection. Though a causative association cannot be established, it does emphasize that with longer survivals on effective antiretroviral therapy, we may see a wide range of malignancies more frequently.